Three MYO15A Mutations Identified in One Chinese Family with Autosomal Recessive Nonsyndromic Hearing Loss - Fengguo Zhang; Lei Xu; Yun Xiao; Jianfeng Li; Xiaohui Bai; Haibo Wang (Neural Plasticity)
Hearing impairment is one of the most common sensory disease, of which more than 50% is attributed to a genetic etiology. The goal of this research is to explore the genetic cause of a Chinese deafness pedigree who was excluded of GJB2, SLC26A4, or MtDNA12SrRNA variants. Three variants, c.3971C>A (p.A1324D), c.4011insA (p.Q1337Qfs∗22), and c.9690+1G>A, in the MYO15A gene were identified by targeted capture sequencing and Sanger sequencing, and the first two of them were novel. These variants were cosegregated with the disease in this family and absent in 200 normal hearing persons. They were concluded to be pathogenic mutations by phylogenetic analysis and structure modeling. Thus, the combined use of SNPScan assay and targeted capture sequencing is a high-efficiency and cost-effective screening procedure for hereditary hearing loss. Genetic counseling would be important for this family, and our finding would be a great supplement to the mutation spectrum of MYO15A.